The relationship between the use of mental health act and elderly suicide rates in England and Walls - Shah, Ajit (Kermanshah University of Medical Sciences, 2009)
BACKGROUND: The relationship between suicide and involuntary admissions has been examined in younger and mixed age groups. These studies provide mixed results with some demonstrating no relationship and others reporting increased rates of suicides in involuntarily admitted patients. This relationship has not been examined in the elderly. METHODS: An ecological study, over the 19-year period, to examine the relationship between rates of involuntary admissions and elderly suicide rates in England and Wales was undertaken using nationally collected data. Data on suicide rates for both sexes in the age-bands 65-74 years and 75+ years were ascertained from the World Health Organization (WHO) website. Data on the number of detentions under the Mental Health Act were ascertained from the Office of National Statistics website. Data on the population size for the elderly age-bands were ascertained from the WHO website. Spearman's correlation coefficient was used to examine the relationship between suicide rates and rates of detention under the Mental Health Act. RESULTS: There were negative correlations between rates of involuntary admissions and suicide rates in both sexes in the age-bands 65-74 and 75+ years. CONCLUSIONS: A causal relationship and the direction of causality cannot be assumed because this was an ecological study. There is a need for sufficiently powered study to compare the number of suicides occurring in involuntarily and voluntarily admitted patients using a case-control or cohort design and survival analysis. If an inverse association can be demonstrated between suicide and involuntary admissions then it has important implications for the development of mental health legislation as an adjunct to national suicide prevention strategies.